Pengaruh Kecerdasan Emosional dan Disiplin Kerja terhadap Kinerja Karyawan pada Platform Candidate College - Refany Novia Siboro; Viki Sulistia (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
Candidate College is a digital platform engaged in education and education to help Indonesian students hone their abilities and skills in the field of education they are interested in. This study aims to analyze the effect of emotional intelligence and work discipline on employee performance on the Candidate College platform. This study provides insight that in order to improve employee performance, the Candidate College platform needs to consider developing programs that not only focus on improving technical skills, but also on improving emotional intelligence and strengthening work discipline. Thus, employees will be better able to manage their emotions and behavior, which will later contribute to improving overall performance. The research method used is quantitative with a descriptive approach and with a sampling technique, namely saturated samples with a sample size of 40 people. Data collection was carried out through questionnaires and interviews with several employees at the Candidate College. The results of the study showed that emotional intelligence and work discipline simultaneously had a significant effect on employee performance on the Candidate College platform. Partially, emotional intelligence has a positive and significant effect on employee performance, while work discipline also has a positive and significant effect on employee performance. The implication of this study is that the management of the Candidate College platform needs to pay attention to and improve employee emotional intelligence and work discipline to encourage optimal employee performance.